(untitled) (Scientia Agropecuaria, 2023)
This study aimed to explore the perception and sensory acceptance of Purple Maize (PM) breakfast cereals by a Brazilian panel. The extrudates were elaborated using 25%, 50%, 75%, and 100% PM in a commercial yellow corn base. A total of 117 consumers evaluated samples through an acceptability test (nine-point hedonic scale) followed by CATA questions (35 descriptive terms) and a market research questionnaire. The cereals formulated with 50% and 75% PM had the best scores (6) in color, aroma, texture, and overall liking during the acceptability test. Based on the penalty-lift analysis, Brazilian consumers’ most important drivers of preference were the attractive color, crispy texture, and the natural and innovative purple color. In contrast, hard texture and brown color drivers negatively impacted the scores. In the market research, consumers indicated that they could eat the product both as a breakfast cereal and as a snack during the day; Likewise, they highlighted the possible health benefits, the innovative color, and the use of exotic raw materials as the best characteristics of the product. Therefore, using 50% PM or more allows for obtaining sustainable and nutritious breakfast cereals with characteristics of color, flavor, and texture well accepted by Brazilian consumers.